Clinical linguistics - Cummings, Louise (Edinburgh University Press, 2008)
An introduction to 'clinical linguistics', a complex field of study that draws upon a range of linguistic, medical and other disciplines. It will introduce students to a wide range of developmental and acquired communication disorders.